P180 External validation of the Southend GCA Probability Score (GCAPS) as a screening tool for referrals with possible GCA. (20th April 2020) - Quick, Vanessa; Hughes, Mark; Mothojakan, Nadira; Fishman, Daniel
Abstract: Background: We run a rheumatologist-led, ultrasound-driven giant cell arteritis (GCA) fast track pathway (FTP). Currently, no specific referral criteria are required. Sensitive referral criteria are now needed to safely reduce referrals, which have risen year-on-year (92 in Year 3, 84% greater than Year 1). Methods: The following were collected for all patients referred to our GCA-FTP from 1/4/2018-31/3/2019 (Year 3): Final diagnosis of imaging/biopsy confirmed-GCA, unconfirmed clinical-GCA or not-GCA using the electronic patient record to September 2019; Rheumatologist-determined clinical probability of GCA (low, moderate, high) before imaging/biopsy; Presence of ≥ 3 ACR 1990 GCA Classification Criteria (biopsy excluded, adapted to increase sensitivity, see table); Presence of Southend GCAPS≥10 (Based on our clinical experience, polymyalgic symptoms were also counted if patients had recently taken prednisolone for PMR). Results: 88 consecutive patients were analysed (total 92: 2 missing data; 2 passed through twice). 25/88 (27%) were diagnosed with GCA 24 were imaging/biopsy confirmed. The single patient with unconfirmed clinical-GCA had high clinical probability, indeterminate ultrasound and biopsy after >1-week glucocorticoid. GCA patients were mean age 77.3y (range 63-94), 76% female, all White, with mean GCAPS 15.3 (range 10-25). Our adaptations of the ACR criteria increased ACR-criteria sensitivity: 24% GCA patients had new generalised headache and 16% had ESR<50, but CRP>10. 14% referrals were non-White, although GCA is rare in this group. GCAPS was based on a largely White population. If GCAPS did not remove 3 points for alternative diagnoses, then 5 additional non-White patients would have scored ≥10. Conclusion: This study externally validates GCAPS≥10 as a screening tool for referrals with possible GCA. It captured all GCA patients and screened out 44% referrals. For this indication, it performed better than a consultant rheumatologist. Despite adaptations to improve sensitivity, ACR criteria missed a quarter of cases. To improve GCAPS specificity when scored by a non-rheumatologist, GCAPS should be adapted to reflect the low likelihood of GCA in non-Whites. We plan to only accept patients with GCAPS≥10, where 3 points are removed for non-Whites if not already removed for alternative diagnoses. We predict referrals will reduce but anticipate referrers will need education to limit over-scoring. Disclosures: V. Quick None. M. Hughes None. N. Mothojakan None. D. Fishman None.